Peran Media Audio-Visual dalam Meningkatkan Hasil Belajar Pendidikan Agama Buddha dan Budi Pekerti Siswa Kelas III A SD Metta Maitreya Pekanbaru - Yadi Sutikno; Rinah Rinah; Dea Elitamala (Jurnal Maitreyawira, 2024)
Three pupils in class III A at Metta Maitreya Elementary School Pekanbaru have yet to meet the Minimum Completion Criteria (MCC) established, according to preliminary observations. Given this observation, a study on how audio-visual materials can improve the learning outcomes of Buddhist Religious Education and Budi Pekerti for class III A students at Metta Maitreya Elementary School Pekanbaru will be carried out. Qualitative research methodology will be employed. The study will be conducted in 2024 between July and September. Metta Maitreya Elementary School, situated on Jln. T. Tambusai, Komp. Puri Nangka Sari, Pekanbaru, Riau, is the research site. The Buddhist Religious Education and Budi Pekerti teacher class III A pupils at Metta Maitreya Elementary School in Pekanbaru, Riau, served as the research's data source. Techniques for gathering data will include documentation, interviews, and observation. According to the study's findings, audio-visual materials help students in class III A at Metta Maitreya Elementary School Pekanbaru learn more effectively in Buddhist Religious Education and Budi Pekerti. This is supported by the study's findings, which show that, when students actively watch and listen to each audiovisual presentation, they can improve the learning outcomes of Buddhist Religious Education and Budi Pekerti for class III A students at Metta Maitreya Elementary School Pekanbaru.